Persistence Probability for a Class of Gaussian Processes Related to Random Interface Models. (March 2015) - Sakagawa, Hironobu
Abstract : We consider a class of Gaussian processes which are obtained as height processes of some ( d + 1)-dimensional dynamic random interface model on ℤ d . We give an estimate of persistence probability, namely, large T asymptotics of the probability that the process does not exceed a fixed level up to time T . The interaction of the model affects the persistence probability and its asymptotics changes depending on the dimension d .